Slovenski jezik in Evropska zveza - Jesenšek, Marko (Slavia Centralis, 2020)
Slovene Language and European UnionThis article presents the position of the Slovene language in the European Union in the context of the European Year of Languages and the European Year of Intercultural Dialogue. Firstly, the experience of the Slovene language in the former common state is presented. Attention is paid to some fictional similarities regarding the position of the Slovene language in the SFRJ and the EU, then the linguistic circumstances and the position of the Slovene language, decisively determined by the multilingualism of the EU in the new community, are analyzed; the advantages and difficulties connected with European multilingualism are presented; and the Slovene linguistic policy as drafted in the Law on Public Usage of Slovene Language and in the Resolution on National Program for Linguistic Policy 2007–2011 is introduced. The article concludes with thoughts on some comments in the Resolution about theposition of Slovene studies in domestic and foreign Universities.
Keywords: European Union; official languages of the EU; multilingualism; position of Slovene language in Yugoslavia and EU; linguistic policy; the Law on public usage of Slovene language; SlangMaster